Sex and Death: Identification of Feedback Neuromodulation Balancing Reproduction and Survival. - Gao, C.; Guo, C.; Peng, Q.; Cao, J.; Shohat-Ophir, G.; Liu, D.; Pan, Y. (Neuroscience bulletin, 2020)
Some semelparous organisms in nature mate as many times as they can in a single reproductive episode before death, while most iteroparous species including humans avoid such suicidal reproductive behavior. Animals naturally pursue more sex and the possible fatal consequence of excessive sex must be orchestrated by negative feedback signals in iteroparous species, yet very little is known about the regulatory mechanisms. Here we used Drosophila male sexual behavior as a model system to study how excessive sex may kill males and how the nervous system reacts to prevent death by sex. We found that continuous sexual activity by activating the fruitless-expressing neurons induced a fixed multi-step behavioral pattern ending with male death. We further found negative feedback in the fly brain to prevent suicidal sexual behavior by expression changes of the neurotransmitters acetylcholine and gamma-aminobutyric acid, and neuropeptide F. These findings are crucial to understand the molecular underpinnings of how different organisms choose reproductive strategies and balance reproduction and survival.